Mobilizing public sociology: scholars, activists, and Latin@ migrants converse on common ground - Carty, Victoria; Luévano, Rafael (Studies in critical social sciences, 2017)
Preface -- Acknowledgments -- Introduction / Victoria Carty -- Immigrant oppression and resistance movements -- Collaboration between federal, state, and local law enforcement : gang injunctions, gang databases, and immigration consequences / Amelia Alvarez and Fawn Bekam -- Gentrification, gang injunctions, and the impact on Latin communities in southern California / Madeleine Spencer and Victoria Carty -- The politics of immigration and a Catholic counternarrative : a perspective from the United States / Kristin E. Heyer -- Embracing the "other" : dreamers navigating higher education / Harriett D. Romo and Raquel R. Marquez -- Immigrants and community narratives -- Latin immigrant youth in the age of mixed messages : a perspective on deferred action and unaccompanied minors / Lisa D. Ramirez -- America's love/hate relationship with immigrants and oc human relations' voice for understanding / Rusty Kennedy -- Public sociology in action : the struggle to assist undocumented Latin youth / Eileen McNerney -- Revolution of the heart : assisting migrants in their quest for dignity / Patrick Murphy -- A life's pursuit : the journey to higher education of an undocumented student / Oliver Lopez -- At the partnership table: bridging academia and community through horizontal dialoguing / Suzanne SooHoo and Patricia Huerta -- Conclusion: the public sociology migrant narrative / Rafael Luevano -- Index